2019
DOI: 10.3390/ijms20153733
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of UCH-L1 Deubiquitinating Activity with Two Forms of LDN-57444 Has Anti-Invasive Effects in Metastatic Carcinoma Cells

Abstract: Normally ubiquitin C-terminal hydrolase L1 (UCH-L1) is expressed in the central nervous and reproductive systems of adults, but its de novo expression has been detected in many human cancers. There is a growing body of evidence that UCH-L1 de-ubiquitinating (DUB) activity plays a major pro-metastatic role in certain carcinomas. Here we tested anti-metastatic effects of the small-molecule inhibitor of UCH-L1 DUB activity, LDN-57444, in cell lines from advanced oral squamous cell carcinoma (OSCC) as well as inva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 80 publications
0
19
0
Order By: Relevance
“…452 Due to the limited aqueous solubility of LDN-57444, its soluble form, LDN-Pox, was then developed and proved to have the potential to treat invasive carcinomas, including EBV-positive malignancies. 453 In addition, a cell-based screening was also used to select compounds inducing cathepsindependent apoptosis. Intriguingly, b-AP15 was identified to induce the accumulation of high-molecular-mass Ub complexes in cells ( Fig.…”
Section: Targeting E3 Enzymesmentioning
confidence: 99%
“…452 Due to the limited aqueous solubility of LDN-57444, its soluble form, LDN-Pox, was then developed and proved to have the potential to treat invasive carcinomas, including EBV-positive malignancies. 453 In addition, a cell-based screening was also used to select compounds inducing cathepsindependent apoptosis. Intriguingly, b-AP15 was identified to induce the accumulation of high-molecular-mass Ub complexes in cells ( Fig.…”
Section: Targeting E3 Enzymesmentioning
confidence: 99%
“…Studies have shown that ubiquitin C-terminal hydrolase L1 (UCH-L1) promotes motility of metastatic HNSCC as well as of extracellular vesicle-mediated transfer of the viral invasive factor LMP1 [66]. Further, Kobayashi et al proved that soluble inhibitors of UCH-L1 are effective in reducing lymph node metastasis of HNSCC; therefore, soluble inhibitors of UCH-L1 offer potential forms of treatment for invasive carcinomas, including EBVpositive malignancies [67].…”
Section: Tde Promote Metastasismentioning
confidence: 99%
“…LDN57444 and LDN91946 are examples of UCHL1-inhibiting isatin O-acyl oximes [219]. Inhibition of UCHL1 activity using LDN5744 or its nanoparticle formulation LDN-POx in vitro shows inhibition of exosome secretions and reduced levels of pro-metastatic factors in exosomal fractions while suppressing the motility of metastatic squamous carcinoma cells and nasopharyngeal cells expressing EBV pro-metastatic latent membrane protein 1 (LMP1) [220]. LDN and LDN-POx treatment also showed decreased carcinoma cell adhesion, reduced pro-metastatic markers, and inhibition of extracellular vesicle-mediated transfer of invasive factor LMP1 [220].…”
Section: Other Small Molecule Dub Inhibitorsmentioning
confidence: 99%